Effects of cardiovascular health, musculoskeletal health and physical fitness on occupational performance of firefighters: protocol for a systematic review and meta-analysis - Andre Pascal Kengne; Denise Smith; Jaron Ras; Elpidoforos Soterakis Soteriades; Lloyd Leach (BMJ Open)
Introduction Firefighting is a hazardous occupation, where firefighters are involved in life-threatening situations, being placed under tremendous physical strain, while wearing heavy and insulated equipment to protect them from chemicals, fumes and high temperatures. This necessitates that firefighter stay in good physical condition and maintain adequate cardiovascular fitness to cope with these stressors and perform their duties with minimal health risks. The aim of this systematic review and meta-analysis is to determine the effect of cardiovascular health, musculoskeletal health and physical fitness on the occupational performance of firefighters.Methods and analysis All study types and designs will be included and appraised. The following electronic databases will be searched: PubMed/Medline, Scopus, Web of Science, Embase, EBSCOHost and CINAHL, with no restrictions on publication date. The literature search will be conducted comprehensively to enable the capturing of as many relevant articles as possible but will be limited to English-language papers only. A combination of the appropriate terms (search string) will be used to ensure the inclusion of the relevant components of the participants, exposure, comparison and outcome. A researcher-generated form with the key characteristics of each study will be used to retrieve all relevant details from the selected studies for initial eligibility screening. The Rayyan Intelligent Systematic Review tool will be used to screen and select studies for inclusion, and information from the included studies will be captured on the researcher-generated data extraction form. The The appraisal tool for cross-sectional studies (AXIS) checklist and the Critical Appraisal Skills Programme toolkit will be used to conduct the methodological assessment of each study. Data will be analysed using Review Manager V.5.3. Generated results will be presented using a combination of figures, graphs and tables. The synthesis of quantitative data (using a meta-analysis methodology) will involve the integration of quantitative findings from multiple studies to achieve coherence.Ethics and dissemination This study obtained ethical clearance from the University of the Western Cape Biomedical Research Ethics Committee (BM21/10/9). We will disseminate the findings of in peer-reviewed journals and at national and international conferences. The protocol will form part of a chapter for a doctoral thesis.PROSPERO registration number CRD42021258898.